Engaged scholarship and public policy decision-making: a scoping review - McIsaac, Jessie-Lee D. (Health Res Policy Syst, 2020)
BACKGROUND: Engaged scholarship includes the coproduction and use of research by partnerships that blend research, policy and/or practice perspectives. This way of doing research attempts to bridge-the-gap between knowledge and its application. Recent reviews have described practices that support engagement and involve the community in research and patients in healthcare but there is less known about how to engage individuals working to inform public policy. AIMS AND OBJECTIVES: The purpose of this research was to articulate the actions and context that support the coproduction and use of research to inform public policy decisions. The study focuses on partnerships between researchers and stakeholders working in public policy across different levels and sectors of government. METHODS: A scoping review methodology was used. Relevant articles were identified from six electronic bibliographic databases of peer-reviewed literature. FINDINGS: A total of 9904 articles were screened and 375 full-text articles were assessed for eligibility. The included 11 studies were from research partnerships internationally and described actions and contextual factors contributing to the coproduction and use of research to inform public policy. Key actions included facilitating frequent interactions with public policy stakeholders, joint planning for research, and collaboration to execute data collection and analysis. Contextual factors included clarity in responsibilities, prior relationships, and mutual respect for partner priorities and perspectives. CONCLUSIONS: Key actions and contextual factors were identified in this review and warrant further study to strengthen research–policy partnerships and their outcomes.